Răspuns:
E.
Explicație pas cu pas:
maximul funcției:
[tex]- \frac{\Delta}{4(m - 1)} = \frac{ {4(m - 1)(m - 3) - (m - 1)}^{2}}{4(m - 1)} = \frac{(m - 1)(4m - 12 - m + 1)}{4(m - 1)} = \frac{3m - 11}{4} \\ [/tex]
[tex]\begin{cases}m - 1< 0 \\ - \frac{\Delta}{4(m - 1)} < 0 \end{cases} \iff \begin{cases}m < 1 \\ \frac{3m - 11}{4} < 0 \end{cases} \iff [/tex]
[tex]\begin{cases}m < 1 \\ 3m - 11 < 0 \end{cases} \iff \begin{cases}m < 1 \\ m < \frac{11}{3} \end{cases}[/tex]
[tex]\implies m \in \Big(- \infty ;1\Big)[/tex]
observăm că pentru m = 1 => -2 < 0, relația este adevărată
[tex]\implies m \in \Big(- \infty ;1\Big) \cup \{1 \}\implies m \in \Big(- \infty ;1\Big] \\ [/tex]